PENGARUH PENGGUNAAN MODEL DISCOVERY LEARNING TERHADAP KETERAMPILAN MENULIS KARANGAN ARGUMENTASI SISWA KELAS X SMA NEGERI 3 PARIAMAN - Tressyalina, Elsalailatun Rozapiah, Syahrul R., (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2017)
In this study, theoretical concept of disovery learning are reviewed the influence model to the writing skills of argumentation of class X students of SMA Negeri 3 Pariaman. The data of this study is the result of the skill of writing the argumentation without and by using the treatment. The data was collected by giving learning of argumentation by using discovery learning model in experiment class. The test used in this study is a test performance to students in the form of writing test of argumentation. Abstract writing skill writing skill and using treatment is compared to see the effect of discovery learning model by using t-test formula. The result of the research shows that (1) writing skill of argumentation of class X students of SMA Negeri 3 Pariaman without using discovery learning model is in qualification Enough, (2) writing skill of argumentation using discovery learning model of class X students of SMA Negeri 3 Pariaman is in Good qualification , (3) based on t-test, it can be concluded that there is significant influence to the discovery learning model in learning writing writing argumentation of class X students of SMA Negeri 3 Pariaman.Â Kata kunci: Pengaruh, penggunaan model discovery learning, menulis karangan argumentasi